2022
DOI: 10.1038/s41531-022-00318-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammatory bowel disease and Parkinson’s disease: A Mendelian randomization study

Abstract: Emerging evidence from observational studies suggests an increased risk of Parkinson’s disease (PD) in patients with inflammatory bowel disease (IBD). However, to date it is not clear whether a causal relationship exists. To investigate whether IBD is causally related to PD, a two-sample Mendelian randomization study was carried out. Independent genetic instruments from the largest available genome-wide association study (GWAS) for IBD (7045 cases, 456,327 controls) including European participants were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…It has also been demonstrated that IBD and PD share common genetic risk profiles, such as CARD15 , LRRK2 , HLA , and MAPT genes ( 71 , 72 ). Notably, a two-sample Mendelian randomization study on IBD and PD genetically predicted that neither IBD nor its subtypes CD and UC were associated with an increased risk of PD ( 73 ), although another Mendelian randomization study confirmed a causal relationship between PD and IBD ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that IBD and PD share common genetic risk profiles, such as CARD15 , LRRK2 , HLA , and MAPT genes ( 71 , 72 ). Notably, a two-sample Mendelian randomization study on IBD and PD genetically predicted that neither IBD nor its subtypes CD and UC were associated with an increased risk of PD ( 73 ), although another Mendelian randomization study confirmed a causal relationship between PD and IBD ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…Freuer et al. conducted an MR study of the association between IBD and PD and reported that genetically predicted IBD was not associated with an increased risk of PD ( 12 ). Unfortunately, their analysis was unidirectional, which means that the question of whether PD can increase the risk of IBD remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…The main features of the included studies were summarized in Table 1 . Of the 14 studies included, nine were cohort studies ( 11 15 , 18 21 ), two cross-sectional studies ( 10 , 22 ), two mendelian randomization studies ( 26 , 27 ) and the remaining one was a case-control study ( 16 ). Altogether, these articles were published between 2011 and 2022, involving more than 13.4 million individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Another a meta-analysis was conducted by Zhu et al ( 25 ) demonstrated that the overall risk of PD was significantly higher in IBD patients than in the general population, with the RR was 1.24 (95% CI:1.15, 1.34, and P < 0.001). In recent years, several clinical studies with large samples have been conducted to investigate the association between IBD and PD, again, with conflicting results ( 10 , 11 , 18 , 19 , 26 , 27 ). In these studies, two (cohort study) reported positive relationships ( 10 , 19 ), while three (two mendelian randomization studies and one cohort study) showed no association ( 18 , 26 , 27 ) and one (cross-sectional study) found an inverse relationship ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation